The feminizing effect of metabolic heating in Green Turtle (Chelonia mydas) clutches in the eastern Mediterranean. Issue 3 (2nd July 2016) - Önder, Betül F.; Candan, Onur
Abstract : Metabolic heating has been poorly investigated in eastern Mediterranean coastline of Turkey, which host some of the most important Green Turtle ( Chelonia mydas ) nesting sites in the Mediterranean. We studied the effects of clutch size and embryo numbers on nest temperature and discuss the feminizing effect of metabolic heating. Two test sites were conducted in Sugözü Beaches (Turkey). Data loggers were placed in eight nests with different clutch sizes. Nest temperature was strongly correlated with embryo numbers and metabolic heating produced by embryos was calculated to be 0.019°C per late stage embryo and 0.020°C per hatchling. Metabolic heating was calculated to be 0.6°C in the middle third of the incubation period during which sex is determined. It was estimated that metabolic heating increased 10.4% of female hatchlings. The heat produced by embryos should be taken into consideration while estimating sex ratios indirectly by nest and sand temperatures. Additionally, the metabolic heating value should be known for conservation measures, such as nest relocation, dividing the nest for controlling nest temperature, especially related to climate change.